Treatment of Mild to Moderate Plaque Psoriasis with Pimecrolimus, Clobetasol, or Calcipotriol Cream: A comparative study - Mshimesh, Bahir A.R. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: a number of studies have shown that application of topical calcineurin inhibitors is effective for a broad spectrum of inflammatory skin disorders. Objective: to compare the efficacy and safety of 1% of pimecrolimus cream versus 0.05% of clobetasol cream and 0.005% of calcipotriol cream in psoriatic patients. Patients and methods: adults on stable plaque psoriasis were randomized to three treatment groups (pimecrolimus, clobetasol, and calcipotriol group). The criteria of inclusion involve affected BSA of ≤10%, with a local psoriasis severity index (LPSI) score of ≥5. The main assessment of clinical efficacy was the percent changes in LPSI. The quantitative determination of cytokine levels (IL -6, s IL-2R, TNF-α), skin biopsies, and creams safety were also evaluated. Results: the median percent changes in LPSI for pimecrolimus, clobetasol and calcipotriol groups were 51%, 56% and 59%, respectively (p>0.05). Pimecrolimus cream decreased cytokines levels and improved pathological features of psoriatic lesion. Mild skin burning was the most frequent adverse event reported by pimecrolimus (40%; p<0.05) versus 8% in clobetasol and 12% in the calcipotriol gr. Conclusion: pimecrolimus cream demonstrated efficacy comparable with that of clobetasol and calcipotriol for the treatment of mild to moderate plaque psoriasis.